Contextual Fear Memory Maintenance Changes Expression of pMAPK, BDNF and IBA-1 in the Pre-limbic Cortex in a Layer-Specific Manner - Chaaya, Nicholas; Wang, Joshua; Jacques, Angela; Beecher, Kate; Chaaya, Michael; Battle, Andrew Raymond; Johnson, Luke R.; Chehrehasa, Fatemeh; Belmer, Arnauld; Bartlett, Selena E. (Frontiers in Neural Circuits, 2021)
Post-traumatic stress disorder (PTSD) is a debilitating and chronic fear-based disorder. Pavlovian fear conditioning protocols have long been utilised to manipulate and study these fear-based disorders. Contextual fear conditioning (CFC) is a particular Pavlovian conditioning procedure that pairs fear with a particular context. Studies on the neural mechanisms underlying the development of contextual fear memories have identified the medial prefrontal cortex (mPFC), or more specifically, the pre-limbic cortex (PL) of the mPFC as essential for the expression of contextual fear. Despite this, little research has explored the role of the PL in contextual fear memory maintenance or examined the role of neuronal mitogen activated protein kinase (pMAPK; ERK 1/2), brain derived neurotrophic factor (BDNF) and IBA-1 in microglia in the PL as a function of Pavlovian fear conditioning. The current study was designed to evaluate how the maintenance of two different long-term contextual fear memories leads to changes in the number of immune-positive cells for two well-known markers of neural activity (phosphorylation of MAPK and BDNF) and microglia (IBA-1). Therefore, the current experiment is designed to assess the number of immune-positive pMAPK and BDNF cells, microglial number and morphology in the PL following CFC. Specifically, two weeks following conditioning, pMAPK, BDNF and microglia number and morphology were evaluated using well-validated antibodies and immunohistochemistry (n=12 rats per group). A standard CFC protocol applied to rats led to increases in pMAPK, BDNF expression and microglia number as compared to control conditions. Rats in the unpaired fear conditioning procedure, despite having equivalent levels of fear to context, did not have any change in pMAPK, BDNF expression and microglia number in the PL compared to the control conditions. These data suggest that alterations in expression of pMAPK, BDNF and microglia in the PL can occur for up to two weeks following CFC. Together the data suggest that MAPK, BDNF and microglia within the PL of the mPFC may play a role in contextual fear memory maintenance.